(untitled) (Research, Society and Development, 2021)
Objective: to identify, through a literature search, the evidence surrounding the importance of feedback, as well as the challenges and paradigms for the exercise of preceptorship and formative feedback in the context of nursing residencies. Method: Research with a qualitative approach, with a descriptive nature, of the Integrative Literature Review typology. Data collection took place based on the following inclusion criteria: Texts with abstracts and available completely online; articles in Portuguese and English; studies published from 2016 to 2021. The question that guided the search was: "What is the evidence in the databases on the exercise of preceptorship in face of formative feedback in nursing homes?". The databases used were Latin American and Caribbean Literature in Health Sciences and Medical Literature Analysis and Retrieval System Online and BDENF – Nursing, through the Virtual Health Library Portal with Descriptors – controlled descriptors – formative feedback; Nursing; Non-medical boarding school; Preceptorship; Nursing Education; Graduate nursing education; and with the keywords – uncontrolled descriptors: Graduate; Feedback and Preceptor. Results: 7 articles were selected, which were analyzed and originated 3 categories. 1) The importance of Formative Feedback in training in residencies; 2) The role of the Nurse preceptor with the residents and with the Formative Feedback and 3) Barriers for the performance of preceptorship in homes and the Formative Feedback process. Final Considerations: From this literature review, it was possible to identify the importance of formative feedback, as well as preceptorship in the environment of nursing homes.